Satellite-particle control technique based on gas-flow-regulation during gas atomization process - HE Xin-yu; LI Xing-gang; Huang Yu-he; ZHU Qiang (Fenmo yejin jishu)
Gas atomization (GA) is an essential method for the preparation of metal powders specifically used in the additive manufacturing. However, there are plenty of “satellites” among the metal powders prepared by GA. The existence of these satellite particles negatively affects the metal additive manufacturing process. In this paper, two gas-flow-regulation strategies, i.e., the introduction of ancillary gas flow and the design of step-shape atomization chamber, were employed to prevent the fine particle entrainment in gas recirculation zone, thus restricting the formation of satellite particles. The evolution of macro flow patterns and particle trajectories were studied based on the numerical simulation by the commercial computational fluid dynamics software ANSYS Fluent. The results show that, the fine particle entrainment in gas recirculation zone can be effectively prevented when the ancillary gas flow is introduced at the position of R/2 (R is the radius of atomization chamber) away from the chamber center with the AAR (the ratio of ancillary flow rate to atomization flow rate) larger than 0.8, or when a step-shaped atomization chamber is employed with a step width of 300 mm and a step height of around 575～600 mm, respectively. Some TC4 titanium alloy powders were prepared by applying the above gas-flow-regulation strategies while their size distribution, sphericity and outgrowth rate were characterized, respectively. The results show that, the outgrowth rate of the powders has been reduced by about 45%, compared with those prepared without the gas-flow-regulation strategies.